Treatment of Digital Ischemia with Liposomal Bupivacaine - José Raul Soberón; Scott F. Duncan; W. Charles Sternbergh (Case Reports in Anesthesiology)
Objective. This report describes a case in which the off-label use of liposomal bupivacaine (Exparel) in a peripheral nerve block resulted in marked improvement of a patient’s vasoocclusive symptoms. The vasodilating and analgesic properties of liposomal bupivacaine in patients with ischemic symptoms are unknown, but our clinical experience suggests a role in the management of patients suffering from vasoocclusive disease. Case Report. A 45-year-old African American female was admitted to the hospital with severe digital ischemic pain. She was not a candidate for any vascular surgical or procedural interventions. Two continuous supraclavicular nerve blocks were placed with modest clinical improvement. These effects were also short-lived, with the benefits resolving after the discontinuation of the peripheral nerve blocks. She continued to report severe pain and was on multiple anticoagulant medications, so a decision was made to perform an axillary nerve block using liposomal bupivacaine (Exparel) given the compressibility of the site as well as the superficial nature of the target structures. Conclusions. This case report describes the successful off-label usage of liposomal bupivacaine (Exparel) in a patient with digital ischemia. Liposomal bupivacaine (Exparel) is currently FDA approved only for wound infiltration use at this time.